2014
DOI: 10.5380/avs.v19i1.32506
|View full text |Cite
|
Sign up to set email alerts
|

HISTOPATHOLOGY ASPECTS AND FIBROSIS EVALUATION OF BOVINE NATURALLY INFECTED LIVERS BY Fasciola hepatica

Abstract: Fasciolosis is a zoonotic disease that infects especially ruminants and the liver damages in chronic infection caused by the parasite are very severe. The aim of this study was to evaluate the histopathological findings in liver of cattle naturally infected with Fasciola hepatica, as well as propose a classification of liver damage caused by this disease based on the chronic inflammation and fibrosis. Were used fragments of the right lobe and left of one hundred livers the cattle. Those fragments were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
4
5
0
Order By: Relevance
“…Ross (1970) reported the injury to the high-calibre bile ducts of bovine due to F. hepatica, nine weeks after artificially infecting animals, accompanied by an increase in thickness of the liver wall, acinar formation with irregular structures on the inner portion and eosinophilic infiltration beyond the outer middle portion. Supporting the current study, Hussain & Zghair (2017) and Trivilin et al (2014) reported haemorrhage points on the parietal surface in chronically infected livers, representing the points of entrance of the immature parasites into the liver structure, and enlarged/distended ducts, caused by immunological reaction of macrophages and lymphocytes infiltration during the later stage of fasciolosis. Oyarzún-Ruiz et al (2019) reported that biliary ducts hyperplasia and hypertrophy with fibroblastic formation, as also observed in infected wild rabbits in Chile.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Ross (1970) reported the injury to the high-calibre bile ducts of bovine due to F. hepatica, nine weeks after artificially infecting animals, accompanied by an increase in thickness of the liver wall, acinar formation with irregular structures on the inner portion and eosinophilic infiltration beyond the outer middle portion. Supporting the current study, Hussain & Zghair (2017) and Trivilin et al (2014) reported haemorrhage points on the parietal surface in chronically infected livers, representing the points of entrance of the immature parasites into the liver structure, and enlarged/distended ducts, caused by immunological reaction of macrophages and lymphocytes infiltration during the later stage of fasciolosis. Oyarzún-Ruiz et al (2019) reported that biliary ducts hyperplasia and hypertrophy with fibroblastic formation, as also observed in infected wild rabbits in Chile.…”
Section: Discussionsupporting
confidence: 84%
“…Supporting the current study, Hussain & Zghair (2017) and Trivilin et al . (2014) reported haemorrhage points on the parietal surface in chronically infected livers, representing the points of entrance of the immature parasites into the liver structure, and enlarged/distended ducts, caused by immunological reaction of macrophages and lymphocytes infiltration during the later stage of fasciolosis. Oyarzún-Ruiz et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 3021 pigs, fascioliasis causes serious hepatic lesions mainly characterized by severe fibrosis [ 14 ]. In addition, periportal fibrosis and collagen deposition around the bile ducts has been also reported in cattle [ 15 , 16 ]. The more chronic injury around the bile ducts, the greater the periportal fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have been observed by Salmo et al, [29] and Okoye et al, [30] in cattle. Trivilin et al, [31] also observed that the liver lesions more prevalent were biliary duct proliferation, mononuclear cell infiltration, arteriosclerosis and periportal and periductal fibrosis.…”
Section: Discussionmentioning
confidence: 93%